Distribute 2 to x and -2, and -6 to x and -2
2(x - 2) = 2x - 4
-6(x - 2) = -6x + 12
2x - 4 = 4x - 6x + 12
Simplify. Combine like terms
2x - 4 = (4x - 6x) + 12
2x - 4 = -2x + 12
Isolate the x. Add 4 to both sides, and 2x to both sides
2x (+2x) - 4 (+4) = -2x (+2x) + 12 (+4)
2x + 2x = 12 + 4
Simplify
4x = 16
Isolate the x. Divide 4 from both sides
4x/4 = 16/4
x = 16/4
x = 4
4 is your answer for x.
hope this helps
Answer:
The third expression: (2x)^3
Step-by-step explanation:
Plug in 3 for x in each expression
2x^3
2(3)^3
Use PEMDAS
2 (3 × 3 × 3)
2 (9 × 3)
2 (27)
54
2x^3 + 5
(The last expression told us 2x^3 = 54 so feel free to use this information to make life easier)
54 + 5
59
(2x)^3
(2 × 3)^3
Use PEMDAS
6^3
6 × 6 × 6
36 × 6
216
(x - 1)^3
(3 - 1)^3
Use PEMDAS
2^3
2 × 2 × 2
4 × 2
8
216 is the greatest value so the third expression is the answer
Answer:
3x3x12= volume of large prism= 108
1x1x12= volume of hole= 12
(Volume of prism)-(volume of hole)= 96
Step-by-step explanation:
Answer: Points (-1 , 7.5), (0 , 6), and (1 , 4.5).
Step-by-step explanation:
First of all, to find the slope, you need to subtract the y's in the numerator over the x's in the denominator. Then you use Y-Y₁=slope(X-X₁) using either of the two points. If you want to simplify it further into slope-intercept form, you need to distribute on the right side of the equation.